Formation of secondary hematite and its role in attenuation of contaminants at mine tailings: review and comparison of sites in Zambia and Namibia - Sracek, Ondra (Frontiers in Environmental Science, 2015)
Mine tailings in African countries Zambia and Namibia have been investigated with an objective to determine the role of secondary hematite in immobilization of contaminants. Two sites, Chambishi and Mindolo, are located in the Copperbelt in Zambia with relatively humid climates and two sites, Berg Aukas and Kombat, are in Namibia, where the climate is semiarid. At the Chambishi site which is about 40 years old, a hardpan composed of hematite and gypsum has formed at a depth of about 60 cm and large amounts of Cu and Co have been deposited. At the much younger Mindolo site (< 10 y), no such hardpan was detected, but hematite is found in iron-rich bands where Cu and Co have also been enriched. At the Berg Aukas site, the V-rich mine tailings are >30 years old, but most V remains in primary descloizite, embedded in a carbonate matrix while a relatively small amount of released V is incorporated into hematite. In contrast, released Zn and Pb are incorporated mainly into smithsonite and cerussite, which are less stable from an environmental viewpoint. Finally, at the Kombat mine tailings (< 5 years old), As released from pyrite is also incorporated into hematite, but Cu released by dissolution of chalcopyrite and bornite has precipitated as malachite, which is less stable than hematite. Water-leached concentrations of contaminants such as Cu, Zn, and Pb (also present in some carbonate phases) are an order of magnitude higher than water-leached concentrations of V and As which are bound to crystalline ferric minerals such as hematite and soluble only in the aqua regia fraction of sequential extraction. It seems that rapid formation of hematite under tropical climate conditions and incorporation of contaminants into this mineral phase is favourable for attenuation of released contaminants. These findings have implications at other mining sites with similar climates in Africa, South America and Asia.